Encouraging Early Outcomes of Treatment With Arsenic Trioxide Combined With Chemotherapy for Alveolar Rhabdomyosarcoma in Children: 4 Case Reports - Peng, Xiaomin; Xiong, Xilin; Li, Yang; Feng, Chuchu; Liu, Hongyan; Wu, Pingping; Li, Chunmou; Weng, Wenjun (Frontiers in Oncology, 2021)
Background: Alveolar rhabdomyosarcoma (ARMS) is a subtype of rhabdomyosarcoma characterized by its aggressive behavior and poor prognosis, highlighting the need for novel treatment options. Arsenic trioxide (ATO) has been shown to specifically inhibit tumor growth and metastasis of ARMS in vitro by acting on the hedgehog pathway. Here we report on a pilot clinical study to evaluate the activity of an ATO combined chemotherapy approach for treatment of ARMS patients . Methods: We designed a therapeutic schedule of an ATO combined chemotherapy, incorporating in comprehensive management according to the Intergroup Rhabdomyosarcoma Study Group protocol. ATO was administered at 0.16 mg/kg per day over 8 hours via an IV for 10 days combined with a chemotherapeutic regimen of vincristine, actinomycin and cyclophosphamide (VAC regimen) on the third day, repeated every 21 days. A total of 8 cycles of ATO combined chemotherapy were applied throughout the entire scheme. Results: A total of 3 refractory/recurrent and 1 untreated ARMS patient, 3 male and 1 femal, with a median age of 5.8 years (range, 5.1 to 12.5 years), were enrolled in the present study. All patients were sensitive to combined chemotherapy with ATO and achieved partial or complete remission during treatment. Except for reversible gastrointestinal reaction and myelosuppression, no other adverse events were observed during the process of treatment. Conclusions: Combined chemotherapy of ATO and a VAC regimen exhibited beneficial activities against ARMS in pediatrics and was well tolerated, but prospective large-scale clinical trials are warranted to determine the long-term efficacy, optimal courses and late toxicity in this population.